The Influence of Green Marketing on Green Satisfaction Mediated By Perceived Quality and Its Impact to Green Trust in Injection Motorcycle - Kurniawan, Shelvy (Journal the Winners: Economics, Business, Management, and Information System Journal, 2014)
Currently, motorcycle manufacturers are increasingly motivated to replace their motorcycle into fuel injection products. The growing concern from the consumers to the environment and the regulations of emission standards, that is Euro 3, for motorcycle industry is being finalized in the Ministry of Environment in order to be implemented in Indonesia. Through this research, the writer will examine the effect of green marketing on perceived quality, green satisfaction, and green trust, the effect of perceived quality on green satisfaction, and the effect of green satisfaction on green trust. Those effects needs to be investigated in order to know how far the effects of green marketing and to ensure whether green marketing is well accepted or not by the market in motorcycle industry. Scope of this research is also limited to the user of fuel injection motorcycle in Jakarta for Honda and Yamaha who involved as decision maker when the motorcycle is purchased. Sampling technique used in this research is quota sampling and the analysis method is structural equation modeling (SEM). The findings of this research are: green marketing has a significant direct effect on perceived quality, perceived quality has a significant direct effect on green satisfaction, green satisfaction has a significant direct effect on green trust, green marketing has a significant direct and indirect effect on green satisfaction, and green marketing has a significant direct and indirect effect on green trust. All of those effects are found to be positive effects.